A Theoretical and Practical Review of the Reconstruction of Guidance Roles and Objectives in Primary Education - Nosi Ageni Putri; Sri Ulandari (EDOVA JOURNAL : Education for Nation Development Journal, 2025)
Guidance in primary schools plays a strategic role in supporting students' holistic development, including academic, social, emotional, and personal aspects. This study aims to analyze the functions, objectives, characteristics, and principles of guidance in primary schools from both theoretical and practical perspectives. Through a literature review, the study finds that the functions of guidance encompass prevention, development, and problem-solving. The objectives are directed toward maximizing students' potential, fostering self-adjustment, and enhancing psychological well-being. The nature of guidance is characterized by flexibility, student-centeredness, and responsiveness to individual needs. Core principles such as confidentiality, openness, and voluntariness serve as essential foundations for implementation. This article also highlights the challenges faced in implementing guidance in primary schools and proposes strategies to enhance its effectiveness. The findings are expected to serve as a reference for educators and counselors in optimizing guidance services to support student development.